African Commission on Human and Peoples' Rights Resolution 234 on the Right to Nationality. (April 2014) - Adjolohoun, Horace S.
Abstract : The right to a nationality is well established in international human rights law. In 1954 and 1961, the United Nations adopted the Convention Relating to the Status of Stateless Persons and the Convention on the Reduction of Statelessness, respectively. Inspired by Article 15 of the Universal Declaration of Human Rights, the two Conventions provide for a right to nationality and prohibit deprivation or denial of nationality. In 2012, the United Nations Office of the High Commissioner for Refugees (UNHCR) drafted four guidelines on statelessness that expand on provisions of the 1954 and 1961 UN Conventions. They contain guidance sections directed specifically at governments, civil society organizations, legal practitioners, decision-makers and the judiciary as well as UNHCR and other UN agency staff involved in addressing statelessness.